A qualificação econômica financeira segundo a Lei 8.666/93: um enfoque nas exigências da administração pública - Coutinho, Renato Lírio (2017)
Characterized as the most advantageous tender selection, when purchasing some good or product of public interest, public bidding is the procedure adopted by the public administration for the acquisition of goods / services throughout the country. Despite the Federal University of Espírito Santo (UFES), it uses this procedure to contract construction / renovation services in all campuses. Given this reason, this dissertation aims to propose a study based on the information of contracting of works and reforms managed by the Management of Works of the University City Hall of UFES, delimiting what are the types of documents required to prove the economic and financial qualification of the bidders, in order to identify if the requirements of proof are in accordance with the established by Law 8666/93 and the Court of Auditors of the Union. The methodology for the collection of bibliographical and jurisprudential data, the following descriptors were used contextualized to the theme In study: qualification of bidders; Public bidding; Law 8666/93, economic and financial qualification; Microenterprises. In addition to the bibliographical research, it was analyzed all contracting of construction works, comprised in the period from 2010 to 2016, of the Federal University of Espírito Santo - UFES. The research sample was based on the construction works and reforms managed by the UFES University Management of Works from 2010 to 2016. Based on the analysis of UFES construction works, six contracts were rescinded by the fact that the companies did not execute the contract, creating injuries to the UFES coffers and, consequently, to the general Public Adminstration. Thus, it suggested the need for better structuring and implementation of control measures of the construction works / reforms carried out in all UFES units has been proven, as well as the application of best practices and training in the teams involved in the bidding processes contracting, in order to guarantee greater criterio in the documentary analysis of the bidders, in order to anticipate risks and avoid prejudice to the public purse. Allowing, the end of the study suggest the implementation of best practices and guidelines in the bidding procedures